2011
DOI: 10.1001/jama.2011.513
|View full text |Cite
|
Sign up to set email alerts
|

Association of CTNNB1 (β-Catenin) Alterations, Body Mass Index, and Physical Activity With Survival in Patients With Colorectal Cancer

Abstract: Context Alterations of WNT-CTNNB1 (β-catenin) signaling play roles in colorectal carcinogenesis and metabolic diseases. Objective To test the hypothesis that CTNNB1 activation in colorectal cancer might modify prognostic associations of body mass index (BMI) and post-diagnosis physical activity. Design We utilized molecular pathological epidemiology (MPE, or molecular pathologic epidemiology) design, investigating interactive effects of tumor and lifestyle factors on tumor behavior. We evaluated CTNNB1 (HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 165 publications
(207 citation statements)
references
References 57 publications
11
193
0
3
Order By: Relevance
“…Given the roles of PDLIM1 in colorectal cancer invasion and metastasis, these findings implicated PDLIM1 as a marker for tumor aggressiveness and a predictor for colorectal cancer patients' survival. Our tissue microarray results also confirmed that low expressions of either E-cadherin or membrane b-catenin were indicators of poor prognosis for colorectal cancer patients, which is compatible with the results of previous studies (22,25). Unlike tumors such as breast cancer where metastasis might take decades to acquire the function for colonization (17), malignant progression and most metastatic traits in colorectal cancer are acquired during progression to the invasive carcinoma stage in the primary site (26).…”
Section: Discussionsupporting
confidence: 91%
“…Given the roles of PDLIM1 in colorectal cancer invasion and metastasis, these findings implicated PDLIM1 as a marker for tumor aggressiveness and a predictor for colorectal cancer patients' survival. Our tissue microarray results also confirmed that low expressions of either E-cadherin or membrane b-catenin were indicators of poor prognosis for colorectal cancer patients, which is compatible with the results of previous studies (22,25). Unlike tumors such as breast cancer where metastasis might take decades to acquire the function for colonization (17), malignant progression and most metastatic traits in colorectal cancer are acquired during progression to the invasive carcinoma stage in the primary site (26).…”
Section: Discussionsupporting
confidence: 91%
“…Given the intrinsic gene-environment interaction between TGF-β and obesity (20,21), we conducted stratified analysis in this study showing that the association between nuclear pSmad2 expression and breast cancer outcome is modified by BMI, with the association predominantly seen among patients who have lower BMI. A similar host-tumor interaction in β-catenin expression and cancer survival was previously shown in a colon cancer study (35).…”
Section: Discussionsupporting
confidence: 80%
“…The methods used to establish this repository are described in detail to motivate and inform future collections of tissue materials in other epidemiologic studies. With tissue samples accrued thus far from 882 participants diagnosed with colon or rectal cancer, the CPS-II colorectal tissue repository is on par with or larger than other tissue collections from comparable prospective cohort studies, including the Nurses' Health Study and Health Professionals Follow-up Study (21)(22)(23), European Prospective Investigation into Cancer and Nutrition (EPIC) (24), the Iowa Women's Health Study (8,25), the Melbourne Collaborative Cohort Study (6,26), the Netherlands Cohort Study (6), and the Northern Sweden Health and Disease Study (27).…”
Section: Discussionmentioning
confidence: 99%